SAT0006 ANTI-TNF agents induce macrophages with pro-resolving phenotype. (15th June 2017) - Degboe, Y; Rauwel, B; Baron, M; Boyer, J-F; Cantagrel, A; Constantin, A; Davignon, J-L
Abstract : Background: Macrophages contribute to the rheumatoid arthritis (RA) pathogenesis. They can display various states of activation or " polarization ", characterized by distinct functions in inflammation, and reversibility depending on their environment [1]. M1 polarization corresponds to the "classical", pro-inflammatory activation as identified in RA. M2 "alternative" polarizations display pro-resolving or wound-healing properties. Data concerning the effects of RA biological drugs (bDMARDs) on macrophage polarization are scarce. Objectives: To assess in vitro modulation of macrophage polarization by RA bDMARDs. Methods: Blood monocytes from 14 healthy donors were positively sorted by CD14+ magnetic selection. Macrophages were Derived from Monocytes (MDM) by 5 days of culture in the presence of MCSF, and activated or not for 24h as M1 pro-inflammatory MDM (by LPS + IFNγ) or as M2 alternative MDM (by IL10 or IL4). MDM were cultured with or without bDMARDs. We evaluated 2 anti-TNF agents (etanercept (ETA), adalimumab (ADA)), 1 anti-IL6R agent (tocilizumab (TCZ)), and 1 anti-CD20 agent (rituximab (RTX)) used as control monoclonal antibody. bDMARDs effects were assessed separately on differentiation and activation phases by flow cytometric analysis of membrane markers. Functional aspects of polarization were assessed by analysis of cytokine production in supernatants (cytometric bead array) and phagocytosis (flow cytometry). MDM cultured in the presence of bDMARDs were compared to untreated MDM by a Wilcoxon matched pairs test. Results: We first validated membranous polarization markers in our culture model: CD40 and CD80 as M1 (LPS + IFNγ) markers; CD16, CD163 and CD64 as M2 (IL10) markers, CD206 and CD200R as M2 (IL4) markers. Anti-TNF significantly modulated surface polarization markers of MDM obtained after differentiation. CD40 decreased with both anti-TNFs. CD16 increased with ADA, whereas opposite effects on CD64, decrease with ETA, increase with ADA, were observed. CD206 increased with ADA. CD200R increased with both anti-TNF. We observed a significant increase in CD64 with TCZ. RTX induced no modulation except an increase in CD64. Concerning the effect of bDMARDs on M1 activation (M1 MDM) shown in Figure, anti-TNF agents induced a significant decrease in M1 markers and a significant modulation in M2 (IL10) markers. We observed a decrease in CD40 and CD80, an increase in CD16, CD163, a decrease in CD64 with ETA and an increase with ADA. TCZ induced a slight but significant decrease in CD40 and an increase in CD64. RTX only affected CD64 as observed for differentiation. In M2 (IL4) et M2 (IL10) activated MDM, anti-TNF agents induced a similar trend toward M2 (IL10) phenotype. Anti-TNF agents led to a significant decrease in TNFα, IL6, IL12 and IL10 levels measured in cell culture supernatant after M1 MDM. TCZ mainly affected IL6 and TNFα productions. No significant effect was observed with RTX. Phagocytosis was superior in M2 (IL10) and M2 (IL4) activated MDM than in M1 MDM. Anti-TNF agents but not TCZ or RTX induced an increase of phagocytosis in M1 MDM. Conclusions: Anti-TNF agents upregulate M2 alternative pro-resolving markers and downregulate M1 inflammatory markers in macrophages. Our results need to be extended by transcriptional analysis and evaluated in RA patients. References: Martinez FO and Gordon S, F1000Prime Reports 2014, 6:13. Disclosure of Interest: Y. Degboe Grant/research support from: Société Française de Rhumatologie, B. Rauwel: None declared, M. Baron: None declared, J.-F. Boyer: None declared, A. Cantagrel: None declared, A. Constantin: None declared, J.-L. Davignon: None declared